2001
DOI: 10.1007/s100510170002
|View full text |Cite
|
Sign up to set email alerts
|

Spin-polarized tunneling in ferromagnetic double barrier junctions

Abstract: Spin-polarized tunneling in FMS/M/FMS double tunnel junctions where FMSs are ferromagnetic semiconductor layers and M is a metal spacer is studied theoretically within the single-site coherent potential approximation (CPA). The exchange interaction between a conduction electron and localized moment of the magnetic ion is treated in the framework of the s-f model. The spin polarization in the FMS layers is observed to oscillates as a function of the number of atomic planes in the spacer layer. Amplitude of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…On further decreasing the temperature, this spin splitting and hence the difference in the barrier heights increases. Therefore, the TMR and spin polarization reach the highest values at T = 0 K. The highest value of the spin polarization for the single SF junction can reach 77%, which is qualitatively in agreement with the experimental measurements [7] and the theoretical results [24,25], while for the double SF junction (in the parallel alignment), it approaches 66% for c = 0.50 nm and 99% for c = 0.72 nm [18], which is due to the change in the positions of the spin-polarized quasibound states in the quantum well. Therefore, one can see that, for the double SF junctions, the TMR and the spin polarization of the tunnelling current can be controlled by the thickness of the central NM layer, the temperature and the applied bias.…”
Section: Numerical Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On further decreasing the temperature, this spin splitting and hence the difference in the barrier heights increases. Therefore, the TMR and spin polarization reach the highest values at T = 0 K. The highest value of the spin polarization for the single SF junction can reach 77%, which is qualitatively in agreement with the experimental measurements [7] and the theoretical results [24,25], while for the double SF junction (in the parallel alignment), it approaches 66% for c = 0.50 nm and 99% for c = 0.72 nm [18], which is due to the change in the positions of the spin-polarized quasibound states in the quantum well. Therefore, one can see that, for the double SF junctions, the TMR and the spin polarization of the tunnelling current can be controlled by the thickness of the central NM layer, the temperature and the applied bias.…”
Section: Numerical Results and Discussionsupporting
confidence: 89%
“…In the previous paper [18], using the single-site approximation for the NM/FMS/NM/FMS/NM double SF junction, we studied the effect of the thickness of the central layer on the spin polarization of tunnel electrons at T =0 K. We showed that the tunnelling spin polarization has an oscillatory behavior with the thickness, which is due to the spin asymmetry of the reflection at the FMS/NM interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation